1979
DOI: 10.3109/01485017908985067
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and fertility in men

Abstract: The possible deleterious effects of folic acid antagonist methotrexate on the fertility potential have been investigated in 26 male psoriatic patients. Examination for semen, testicular histology, and spermatogenic function using radioactive phosphorus revealed that methotrexate had no unfavorable effect on male fertility. A long follow up of the patients and their offspring is needed to exclude the possible teratogenic effect of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…66 No increases in abnormal births have been documented with fathers on methotrexate. [67][68][69] Several possible explanations have been put forth. The oligospermia may be severe enough to inhibit fertilization.…”
Section: Effect Of Low-dose Methotrexate On Male Fertility and Spermamentioning
confidence: 99%
See 1 more Smart Citation
“…66 No increases in abnormal births have been documented with fathers on methotrexate. [67][68][69] Several possible explanations have been put forth. The oligospermia may be severe enough to inhibit fertilization.…”
Section: Effect Of Low-dose Methotrexate On Male Fertility and Spermamentioning
confidence: 99%
“…70 Other studies revealed no changes in spermatogenesis and sperm counts. 68,71 Since one cycle of spermatogenesis requires 74 days, the conservative recommendation is to wait 3 months prior to conception to allow for the effects of methotrexate to completely pass. Based on the current evidence, it may be less likely for a man to conceive a child while exposed to low-dose methotrexate.…”
Section: Effect Of Low-dose Methotrexate On Male Fertility and Spermamentioning
confidence: 99%
“…Although some studies suggest that methotrexate treatment may result in severe, yet reversible, oligospermia despite normal hormone levels, 53 other studies reveal no changes in spermatogenesis and sperm counts. 54,55 One cycle of spermatogenesis requires 74 days thus it is appropriate for male patients to wait 3 months after discontinuing methotrexate before attempting to conceive a child to allow for the methotrexate effects to be eliminated.…”
Section: Male Fertilitymentioning
confidence: 99%
“…Fertility should be restored in men who stop taking methotrexate or sulfasalazine 3 months before trying to conceive. 59,60 Health Maintenance Measures Primary care physicians and gastroenterologists need to work in tandem to cover the health maintenance needs of patients with IBD. Issues surrounding appropriate vaccinations should be addressed at the time of diagnosis.…”
Section: Pregnancy and Family Planningmentioning
confidence: 99%